Effects of phosphate-solubilizing fungi on phosphorus availability, retention, and soil chemical properties in shallot cultivated on andisols of North Sumatra - Marpaung, Agustina Erlinda; Sabrina, Tengku; Rauf, Abdul; Susilowati, Dwi Ningsih (Universitas Padjadjaran, 2026)
The availability of phosphorus (P) is one of the main limiting factors for plant productivity in Andisol soils due to the strong fixation of P by allophane clay minerals, aluminum and iron oxides. Giving the phosphate solubilizing fungi (PSF) is an alternative to increase available P which plants can use to increase the yield. This study aimed to evaluate the effectiveness of phosphate-solubilizing fungi (PSF) in improving P availability on Andisol. The experiment used a block randomized design (BRD) with three replications. The first factor is Andisol soil origin (Soil 1 and Soil 2) and the second is isolate of phosphate solubilizing fungi (Aspergillus niger P13, A. niger P21, A. pseudodeflectus BJ21, and A. niger BJ23). The research results showed that Soil 1 generally produces higher growth and yield of shallots than soil 2. A. pseudodeflectus BJ21 can increase available P by 48.46% and A. niger P13 by 45.71% compared to without phosphate solubilizing fungi. A. niger P13 can reduce P retention by 18.48% compared to without phosphate solubilizing fungi. A. niger BJ23 can increase plant P uptake by 35.35% compared to without phosphate solubilizing fungi. Inoculation of isolates A. niger P13 and A. pseudodeflectus BJ21 was able to adapt and grow well on Andisol soil which significantly increased the population compared to the control. Indigenous phosphate-solubilizing fungi (A. niger and A. pseudodeflectus) improved P availability and uptake in Andisol, reduced P retention, adapted well to the soil environment, and showed strong potential as environmentally friendly biofertilizers based on local resources.